The Amazon Epiphyte Network: A First Glimpse Into Continental-Scale Patterns of Amazonian Vascular Epiphyte Assemblages - Quaresma, Adriano; Zartman, Charles E.; Piedade, Maria T. F.; Wittmann, Florian; Jardim, Mario A. G.; Irume, Mariana V.; Benavides, Ana M.; Freitas, Leandro; Toledo, José J.; Boelter, Carlos R.; Obermüller, Flávio; Duque, Alvaro J.; et al. (Frontiers in Forests and Global Change, 2022)
Epiphytes are still an understudied plant group in Amazonia. The aim of this study was to identify distributional patterns and conservation priorities for vascular epiphyte assemblages (VEA) across Amazonia. We compiled the largest Amazonian epiphyte plot database to date, through a multinational collaborative effort of 22 researchers and 32 field sites located across four Amazonian countries - the Amazonian Epiphyte Network (AEN). We addressed the following continental-scale questions by utilizing the AEN database comprising 96,448 epiphyte individuals, belonging to 518 vascular taxa, and growing on 10,907 tree individuals (phorophytes).Our objectives here are, first, to present a qualitative evaluation of the geographic distribution of the study sites and highlight regional lacunae as priorities for future quantitative inventories. Second, to present the floristic patterns for Amazonia-wide VEA and third, to combine multivariate analyses and rank abundance curves, controlled by major Amazonian habitat types, to determine how VEA vary geographically and ecologically based on major Amazonian habitat types. Three of the most striking patterns found are that: 1) VEA are spatially structured as floristic similarity decays with geographic distance; 2) a core group of 22 oligarchic taxa account for more than a half of all individuals; and 3) extensive floristic sampling gaps still exist, mainly across the highly threatened southern Amazonian deforestation belt. This work represents a first step towards unveiling distributional pattern of Amazonian VEA, which is important to guide future questions on ecology and species distribution ranges of VEA once the collaborative database grows allowing a clearer view of patterns.